Perancangan Sistem Informasi Pengendalian E-Skripsi Untuk Dosen Dan Mahasiswa Berbasis Web - Genda Prasetia; Ifan Junaedi; Anton Zulkarnain Sianipar (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
In the world of education, it is very necessary to have the sophistication of existing technology to take advantage of it, special skills are needed. Likewise with the lectures at STMIK Jayakarta, especially in the information systems study program. the technology that is already there is very helpful for the entire existing management. Students also play an important role in the world of education. Of course, to get a bachelor's degree (S1), students must pass the rules that exist on campus. Especially for the S1 degree for the Information Systems study program, following the rules that have been set in the information systems study program, of course passing the final phase, namely the final project or also called Thesis. Sometimes because students are lazy to go to campus, it takes a long time to complete their final assignments. The final project is mandatory for all students to be able to get the title and to prove that they have studied as well as possible in the world of lectures. To carry out the thesis, students must come all the way to campus and deal with the study program first to find out that the title has been approved by the study program and find out who the supervisor is concerned with the title. The problem in the Information Systems Study Program for the final project is that sometimes the title submitted by students is not detected between the titles in the study program and those on the internet, then students can change the title without the study program's knowledge and also change the supervisor without the information systems study program knowledge.